Colonic Histoplasmosis Presenting as Polyps in an Asymptomatic Patient With Liver Transplant. Issue 5 (18th May 2021) - Cui, Min; Wong, Richard C.K.; Gholam, Pierre M.
ABSTRACT: Infection of the gastrointestinal tract by Histoplasma capsulatum is generally considered to be a manifestation of disseminated disease. The most common symptoms from gastrointestinal histoplasmosis include abdominal pain and diarrhea. Isolated asymptomatic gastrointestinal histoplasmosis is unusual, and diagnosis can be challenging. We report a 57-year-old man with a history of liver transplant presented with numerous colonic polyps, and the biopsies demonstrated granulomatous colitis with fungal microorganism consistent with H. capsulatum . Antigen/antibody tests for Histoplasma were confirmatory. The patient was asymptomatic with no clinical or radiological evidence of pulmonary involvement. He responded well to itraconazole treatment, and urine antigen tested negative 6 months after the initiation of the treatment. Follow-up colonoscopy performed 12 months after treatment with itraconazole showed no evidence of colonic histoplasmosis.